A review on the classification, preparation of nutraceuticals and their application - Farakh Munir; Urvah Asif (AMMANIF, 2018)
Nutritional health products are a powerful tool for maintaining and improving human health. They can fight against acute and chronic diseases caused by nutrition deficiency that promote quality effectiveness of human life. Nutritional therapeutic properties are needed to improve human health but due to their poor bioavailability and depending on their chemical instability to pH, oxygen, temperature and absorption of food ingredients, and also their low intake and low gastrointestinal absorption, the nutritional health benefits still lag behind their potential. Some of these limitations can be resolved by using micron and nanocapsulation technologies that can provide new delivery systems to many food industry, enriching foods and beverages with nutraceuticals. Micron and nanoencapsules of nutritional products provide large variety of advantages related to their stability like thermal, pH, in vitro performance, improved bioavailability and biological activity. Nanocarriers like liposomes, Nanoemulsion, lipids and polymer nanoparticles, micelles and cyclodextrins complex used for the administration of nutritional products.